TRANSLATIONAL STUDY OF ENGLISH AND UZBEK NEWS HEADLINES - Turgunova, Fazilat; Ilxom, Rustamov (Журнал иностранных языков и лингвистики, 2021)
It is discussed the role of major cultural dictionaries in translators life in this article. It also reviews foreign schientists research on this topic.